High-performance high-temperature chain oil composition and preparation method thereof
By using materials such as alkyl naphthalene, dipentaerythritol triphenyl sulfide ester and modified N-phenyl-α-naphthylamine in high-temperature chain oil, combined with modified nano black phosphorus, the easy oxidation and flash point of high-temperature chain oil is solved. The low problem improves oxidation and wear resistance, extends service life and reduces safety hazards.
Patent Information
- Application Number
- CN202411398016.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The existing high-temperature chain oil is prone to oxidation in high temperature environments, has low flash point, and has serious coking carbon deposits, resulting in safety hazards and short service life, and insufficient oxidation resistance and extreme pressure wear resistance.
Using alkyl naphthalene base oil, dipentaerythritol triphenyl sulfide ester base oil and modified N-phenyl-α-naphthylamine and hindered phenol, combined with modified nano black phosphorus and supported catalysts, through chemical bonds and gels The structure improves the high and low temperature resistance of chain oil, and enhances oxidation and wear resistance.
It significantly improves the oxidation resistance, extreme pressure wear resistance and service life of high-temperature chain oil, reduces evaporation loss and coking amount, and enhances the stability and safety of the oil.
Smart Images

Figure CN119286572A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lubricating oils, in particular to a high-performance high-temperature chain oil composition and a preparation method thereof. Background Art
[0002] With the rapid development of industries such as petrochemicals, textiles, printing and dyeing, building materials and transportation, the power and operating speed of processing equipment are constantly increasing, the operating temperature of the transmission system is getting higher and higher, and the requirements for chain oil are becoming more and more stringent. High-temperature chain transmissions work in an environment exposed to high and low temperatures. The temperature of high-temperature chain oil is generally 220-260℃, and the lubricating oil is very easy to oxidize. Therefore, it is very important for the chain lubricating oil to have high high-temperature oxidation stability and good lubricity at high temperatures. High-temperature chain oil with excellent oxidation stability can prevent the lubricating oil from high-temperature decomposition, polymerization, coking, and evaporation under high-temperature operation conditions. It has good lubrication performance and can extend the service life of the chain, reduce the maintenance cycle, and thus improve production efficiency.
[0003] In order to improve the anti-oxidation and anti-wear properties of lubricating oil and reduce the coking and carbon deposition of lubricating oil in high-temperature chains, patent CN107304378B discloses a high-temperature chain oil composition and a preparation method thereof, which is prepared by reacting aniline, sulfur chloride and 4-chloroaniline to generate an intermediate, and then subjecting the intermediate to a nucleophilic substitution reaction to synthesize an antioxidant and anti-wear multi-effect additive, as shown in Formula I. The added antioxidant and anti-wear multi-effect additive and the thiophenol ester antioxidant are used in synergistic manner to improve the antioxidant and anti-wear properties of the high-temperature chain oil composition.
[0004]
[0005] Patent CN107304377B discloses a high-temperature chain oil composition and a preparation method thereof. The invention uses lubricating oil base oil, antioxidant multi-effect additives, 2,2'-thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)]ethyl propionate, zinc oxide nanoparticles, and demulsifiers as raw materials to prepare the composition. The structure of the antioxidant multi-effect additive is shown in Formula II. The high-temperature chain oil composition has good anti-wear and antioxidant properties.
[0006]
[0007] Patent CN106590847B discloses a high-temperature chain oil composition and a method for manufacturing the same. The invention creatively adds a shielded phenol compound, whose structure includes but is not limited to the following formula. At the same time, extreme pressure anti-wear agents, rust inhibitors and base oils are also added. The obtained high-temperature chain oil composition has good antioxidant properties, low coke plate test deposits, and is wear-resistant and rust-resistant.
[0008]
[0009] The above patents all improve the antioxidant performance, anti-wear performance and anti-coking and carbon deposition performance of the chain oil composition by synthesizing compounds containing elements or functional groups such as benzene rings, phenolic hydroxyl groups, imino groups, sulfur, etc. However, phenolic antioxidants have good antioxidant effects, but low operating temperatures, while amine-type antioxidants have higher operating temperatures and better durability, but are prone to discoloration and precipitation, thereby increasing the amount of coking. In addition, the low-temperature resistance of the composition is poor; the prepared antioxidant has poor compatibility with the base oil, and long-term use is likely to cause a decrease in the stability of the high-temperature chain oil composition, thereby affecting the comprehensive performance of the high-temperature chain oil composition.
[0010] Patent CN105838484B discloses a high-temperature chain oil composition and a preparation method thereof. Dipentaerythritol ester and aromatic ester are used as base oils, and alkoxy phosphate extreme pressure anti-wear agents, oiliness agents, viscosity index improvers, antioxidants, and corrosion inhibitors are added to prepare the high-temperature chain oil composition. The obtained chain oil composition has excellent high-temperature performance, no carbon deposition, and good wear resistance and friction reduction performance.
[0011] At present, high-performance high-temperature chain oils are still facing the following problems in actual use: low flash point, resulting in a reduced safety factor, which is easy to cause safety accidents; serious coking and carbon deposition; poor lubrication effect, poor extreme pressure and wear resistance, resulting in a short service life of the chain; in high-temperature use environments, evaporation loss is fast and the evaporation loss is large, and the antioxidant performance is seriously reduced.
[0012] To this end, a high-performance high-temperature chain oil composition and a preparation method thereof are proposed. Summary of the invention
[0013] The object of the present invention is to provide a high-performance high-temperature chain oil composition and a preparation method thereof. A base oil, an antioxidant and an anti-wear agent are prepared and used in combination with other additives to obtain a high-temperature chain oil composition. Anti-wear agent 1 is prepared and used in combination with modified nano black phosphorus to obtain an anti-wear agent, thereby improving the extreme pressure wear resistance of the composition. Alkyl naphthalene base oil is prepared by using a supported catalyst, and the prepared dipentaerythritol triphenyl sulfide ester base oil and low-viscosity polyalphaolefin are used as base oils together, so that the conversion rate of naphthalene in the alkyl naphthalene base oil is high, and the chain oil composition has a high kinematic viscosity index and good high temperature and low temperature resistance. Modified N-phenyl-α-naphthylamine is prepared and used in combination with a hindered phenol antioxidant, and the amount of components of the chain oil composition is changed at the same time, so that the composition has good antioxidant effect, small evaporation loss and is not easy to produce precipitation.
[0014] To achieve the above object, the present invention provides the following technical solutions:
[0015] In one aspect, the present invention provides a method for preparing a high-performance high-temperature chain oil composition, comprising the following steps:
[0016] 70-92 parts of base oil, 0-4.5 parts of antioxidant (modified N-phenyl-α-naphthylamine and hindered phenol mixed in a ratio of 3:1), 0-2.5 parts of anti-wear agent, 1 part of anti-corrosion agent, and 0.5 parts of dispersant are mixed, the temperature is adjusted to 60° C., and stirred evenly to obtain the high-performance high-temperature chain oil composition;
[0017] The anti-wear agent is a mixture of an anti-wear agent 1 and modified nano black phosphorus in a mass ratio of 1-17:1; the heating temperature of the thiophosphoric acid precursor in the anti-wear agent 1 is 60-95°C; the molar ratio of isooctyl alcohol to phosphorus pentasulfide is 1.1-1.3:1; the pH of the phosphate buffer solution in the maleimide-PEG6 solution is 6.5-7.2; the molar ratio of thiophosphoric acid to bismaleimide-PEG6 is 1:1.1-1.2;
[0018] The base oil is obtained by mixing alkyl naphthalene base oil, dipentaerythritol triphenyl sulfide ester base oil and low-viscosity polyalphaolefin in a ratio of 1-4:1-6:5-13 and then vacuum drying;
[0019] The kinematic viscosity of low viscosity polyalphaolefin at 100°C is 1.7 mm 2 / s, the kinematic viscosity at 40℃ is 5.1mm 2 / s.
[0020] The alkyl naphthalene base oil is prepared by dispersing a Y-type molecular sieve in anhydrous ethanol, adding 0.1-0.4 parts of sulfated zirconium oxide thereto, and ultrasonically obtaining a supported Y-type molecular sieve dispersion; adding naphthalene and tetradecene to 5.5-8.7 parts of the supported Y-type molecular sieve dispersion, separating the liquids after the reaction, and performing reduced pressure distillation to obtain the supported Y-type molecular sieve dispersion;
[0021] The dipentaerythritol triphenyl sulfide ester base oil is obtained by reacting dipentaerythritol, 0-250 parts of triphenyl sulfide acid, concentrated sulfuric acid and 150-750 parts of lithium water glass solution;
[0022] Alkylnaphthalene base oil has the characteristics of both alkyl and naphthalene, and has high high temperature resistance. By reacting triphenyl sulfide acid and lithium water glass with dipentaerythritol respectively, the triphenyl sulfide acid introduced by chemical bonds contains not only multiple benzene rings but also a sulfide structure, so that the chain oil composition has high high temperature resistance. In addition, the added lithium water glass is dissolved in the sodium hydroxide solution to form sodium silicate and lithium hydroxide. Under heating conditions, the sodium silicate undergoes a hydrolysis reaction and cross-links with dipentaerythritol to form a three-dimensional gel structure, and the lithium element is evenly arranged in the gel structure. The introduced silicon and lithium elements improve the high temperature resistance and low temperature resistance of the chain oil composition.
[0023] The modified N-phenyl-α-naphthylamine is obtained by reacting 98.6-102.4 parts of benzothiazolethiohydroxybenzene bromide, a copper chromite catalyst, 44 parts of N-phenyl-α-naphthylamine and 16.8-17.5 parts of crotonic acid.
[0024] The corrosion inhibitor includes, but is not limited to, benzotriazole octadecylamine salt, 2-methyl-isothiazol-3(2H)-one and 2-chloro-1,3-dimethylimidazoline chloride, zinc molybdate, methylbenzotriazole, N-di-n-butylaminomethylenebenzotriazole, and methylenebenzotriazole.
[0025] Dispersants include, but are not limited to, high base sulfurized alkylphenol salts (400 mgKOH / g), ethylene oxide-propylene oxide copolymers, sulfurized olefin cottonseed oil, sulfurized cyclohexanol cottonseed oil, triphenyl phosphite, sulfurized whale oil, sulfurized cotton, and dimer acid.
[0026] Preferably, the preparation method of the anti-wear agent comprises the following steps: in terms of molar ratio, reacting the isooctyl alcohol with 1 / 3 of the phosphorus pentasulfide to obtain a thiophosphoric acid precursor; heating the thiophosphoric acid precursor, adding 2 / 3 of the phosphorus pentasulfide thereto, and reacting to obtain the thiophosphoric acid; adding the thiophosphoric acid and tris(2-carboxyethyl)phosphine catalyst to the bismaleimide-PEG6 solution, raising the system temperature to 50°C, and stirring for 2 hours under nitrogen protection to obtain an anti-wear agent precursor; adding XC-DAPOL-CPBA to the anti-wear agent precursor, adding a catalyst, adjusting the pH, and then heating, and reflux reaction for 10 hours to obtain the anti-wear agent one; mixing the anti-wear agent one and the modified nano black phosphorus, and grinding to an average particle size of 170 nm to obtain the anti-wear agent.
[0027] Among them, the structure of XC-DAPOL-CPBA is shown as follows:
[0028]
[0029] Preferably, the preparation method of the modified nano black phosphorus is as follows: disperse the nano black phosphorus in a potassium permanganate solution at 70° C., stir for 2 hours, filter, and wash with deionized water to obtain pre-treated nano black phosphorus; add phenylboric acid to the pre-treated nano black phosphorus, grind for 5 hours, and then dry to obtain the modified nano black phosphorus.
[0030] Nano black phosphorus has a similar two-dimensional structure to graphene. The layers are connected by van der Waals forces, which makes interlayer sliding easy and has good wear resistance. However, as an inorganic substance, it has poor compatibility with the chain oil composition and is easily oxidized. After surface oxidation treatment, phenylboric acid is used to modify its surface to improve its compatibility with the components. In addition, during the subsequent heating and stirring process, phenylboric acid can react with the unreacted maleimide in bismaleimide-PEG6 to undergo an addition reaction, thereby introducing the modified nano black phosphorus into the anti-wear agent through chemical bonds.
[0031] Preferably, the preparation method of the dipentaerythritol triphenyl sulfide ester base oil is as follows: add the dipentaerythritol into a three-necked flask, then add the triphenyl sulfide acid, raise the temperature to 100°C, adjust the vacuum degree to 98.8 KPa, then add the concentrated sulfuric acid and activated carbon powder, and react for 8 hours to obtain a base oil precursor; dissolve lithium water glass in sodium hydroxide solution to obtain the lithium water glass solution; add the lithium water glass solution to the base oil precursor and continue to react for 6 hours, then cool to room temperature, and filter to obtain the dipentaerythritol triphenyl sulfide ester base oil.
[0032] Preferably, the modulus of the lithium water glass is 3.5.
[0033] Preferably, the preparation method of the modified N-phenyl-α-naphthylamine is as follows: dissolving the benzothiazolethiohydroxybenzene bromide in an acetone solution to obtain a benzothiazolethiohydroxybenzene bromide solution; heating the benzothiazolethiohydroxybenzene bromide solution to 140°C, adding sodium hydroxide and the copper chromite catalyst thereto to obtain a reaction solution; stirring the reaction solution for 12 hours, cooling it to room temperature and then filtering it, then washing and drying it to obtain benzothiazolethiohydroxyphenol; adding the N-phenyl-α-naphthylamine to a closed reactor, then adding the crotonic acid and the zero-valent ruthenium catalyst thereto, reacting at 130°C for 7 hours to obtain a modified N-phenyl-α-naphthylamine intermediate; adding the benzothiazolethiohydroxyphenol and concentrated sulfuric acid to the modified N-phenyl-α-naphthylamine intermediate, continuing the reaction for 4 hours, adding deionized water, washing it several times and then drying it to obtain the modified N-phenyl-α-naphthylamine.
[0034] Wherein, the structural formula of the benzothiazolethiohydroxybenzene bromide is shown as follows:
[0035]
[0036] Preferably, the amount of the antioxidant is 3.8-4.5 parts.
[0037] Preferably, the amount of the antiwear agent is 1.5-2.5 parts.
[0038] Preferably, the hindered phenol is any one of 1,1'-dithiodi(2-naphthol), 2,2',4,4'-tetrahydroxydiphenyl sulfide and 2,2-dihydroxydiphenyl sulfide. The structural formulas thereof are shown in the following formula:
[0039]
[0040] On the other hand, the present invention provides a high-performance high-temperature chain oil composition, the high-performance high-temperature chain oil composition comprises a base oil, an antioxidant, an anti-wear agent, a corrosion inhibitor and a dispersant; the high-performance high-temperature chain oil composition is prepared by any one of the preparation methods described above; the high-performance high-temperature chain oil composition P B The value is 392-1236N, the wear scar diameter is 0.28-0.51mm; the conversion rate of naphthalene in the alkyl naphthalene base oil is 90.1%-95.6%; the kinematic viscosity of the high-performance high-temperature chain oil composition at 40°C is 232.4-375.2mm 2 / s, kinematic viscosity at 100℃ is 24.4-34.8mm 2 / s; the VI value of the high-performance high-temperature chain oil composition is 89-123, the flash point is 249-279°C, and the pour point is -20 to -31°C; the initial oxidation temperature of the high-performance high-temperature chain oil composition is 237.9-260.5°C, the oxidation induction time at 210°C is 13.6-82.9min, and the coking amount is 12-40mg; the evaporation loss of the high-performance high-temperature chain oil composition is 1.98%-2.86%, the initial oxidation temperature is 235.0-265.4°C, the oxidation induction time is 21.5-98.9min, and the coking amount is 6-38mg.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] 1. By reacting isooctyl alcohol with phosphorus pentasulfide, adding phosphorus pentasulfide to the reaction system in batches, controlling the reaction temperature, obtaining thiophosphoric acid, and then adding bismaleimide-PEG6 under neutral conditions, the unsaturated double bond of maleimide in bismaleimide-PEG6 reacts with the thiol group of thiophosphoric acid, and the unreacted maleimide group reacts with the boric acid connected to the benzene ring in XC-DAPOL-CPBA, thereby obtaining antiwear agent 1. Modified nano black scale is obtained by surface modification of nano black scale. The antiwear agent 1 is used in combination with nano black scale to obtain a high-performance high-temperature chain oil composition with excellent extreme pressure performance and wear resistance.
[0043] 2. The supported Y-type molecular sieve is prepared and used for catalytic synthesis of alkylnaphthalene base oil, thereby improving the conversion rate of raw material naphthalene. By using dipentaerythritol as the reaction raw material, the carboxyl group of triphenyl sulfide acid undergoes esterification reaction with the hydroxyl group of dipentaerythritol at high temperature, thereby connecting through chemical bonds, and then reacting the lithium water glass solution with dipentaerythritol to prepare dipentaerythritol triphenyl sulfide ester base oil. The alkylnaphthalene base oil, dipentaerythritol triphenyl sulfide ester base oil and polyalphaolefin are used in combination to further obtain a high-performance high-temperature chain oil composition with high kinematic viscosity.
[0044] 3. By synthesizing alkyl naphthalene base oil and using it in combination with the prepared dipentaerythritol triphenyl sulfide ester base oil, the presence of naphthalene, benzene ring structure, silicon and lithium elements in the base oil makes the high-performance chain oil composition have good high temperature resistance and low temperature resistance, and the composition is less affected by temperature.
[0045] 4. Replace the bromine in benzothiazolethiohydroxybenzene bromide with a hydroxyl group, and then modify N-phenyl-α-naphthylamine with benzothiazolethiohydroxyphenol. After the double bond of butylene acid and the double bond of the naphthalene ring in N-phenyl-α-naphthylamine undergo a hydrogenation reaction, the hydroxyl group of benzothiazolethiohydroxyphenol reacts with the unreacted carboxyl group of butylene acid to generate modified N-phenyl-α-naphthylamine. The modified N-phenyl-α-naphthylamine has good antioxidant capacity and reduced coking.
[0046] 5. The high-performance high-temperature chain oil composition prepared by the present invention has good antioxidant performance, low coking amount and low volatility by reasonably adjusting the amount of base oil, antioxidant, anti-wear agent and the type of hindered phenol in the antioxidant. By adjusting the amount of the base oil synthesized by the present invention, the high-performance high-temperature chain oil composition has low volatility and stable performance. In addition, the modified N-phenyl-α-naphthylamine and hindered phenol, as well as the sulfur phosphate in the anti-wear agent, work synergistically to achieve good antioxidant effect. In addition, the high-performance high-temperature chain oil composition is not easy to produce precipitation during use. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is a graph showing the conversion rate of naphthalene in the alkylnaphthalene base oil of Example 34 of the present invention;
[0048] Figure 2 This is a graph showing the evaporation loss results of the high performance and high temperature chain oil composition of Example 56 of the present invention;
[0049] Figure 3 This is a graph showing the coking amount results of the high performance and high temperature chain oil composition of Example 56 of the present invention. DETAILED DESCRIPTION
[0050] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] See also Figures 1 to 3 The present invention provides a high-performance high-temperature chain oil composition and a preparation method thereof, and the technical scheme is as follows:
[0052] The substance information involved in the present invention is as follows:
[0053] XC-DAPOL-CPBA, CAS: 191231-97-7; Bismaleimide-PEG6, CAS: 2752168-26-4; Triphenylsulfide acid, CAS: 124243-00-1; Benzothiazolethiohydroxybenzene bromide CAS: 441292-31-5; Tris(2-carboxyethyl)phosphine, CAS: 51805-45-9; Rhodium-carbon catalyst, CAS: 7440-16-6; Benzene Boric acid, CAS: 98-80-6; dipentaerythritol, CAS: 126-58-9; 1,1'-dithiodi(2-naphthol), CAS: 17096-15-0; 2,2',4,4'-tetrahydroxydiphenyl sulfide, CAS: 97-29-0; 2,2-dihydroxydiphenyl sulfide, CAS: 13693-59-9; naphthalene, CAS: 91-20-3; tetradecene, CAS: 1120-36-1. Nano black phosphorus was purchased from Xi'an Qiyueyang Biological Co., Ltd.; low viscosity polyalphaolefin was purchased from Shanghai Daopu Chemical Co., Ltd.; Y-type molecular sieve was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0054] Other reagents, substances and instruments not specified are all commercially available products in the field of conventional chemical experiments.
[0055] Examples 1-12
[0056] In a reaction vessel equipped with a stirrer, a reflux condenser and a thermometer, under nitrogen protection, isooctyl alcohol is added to the reaction vessel, the temperature is raised to 60°C, and then 1 / 3 of a molar amount of phosphorus pentasulfide is added thereto, and the reaction is carried out for 3 hours to obtain a thiophosphoric acid precursor; the thiophosphoric acid precursor is heated, and the remaining 2 / 3 of a molar amount of phosphorus pentasulfide is added thereto, and the reaction is refluxed for 15 hours, and the thiophosphoric acid is obtained by filtration and purification after cooling; the molar ratio of isooctyl alcohol to phosphorus pentasulfide is 1.1-1.3:1; bismaleimide-PEG6 is dissolved in a phosphate buffer solution to obtain a bismaleimide-PEG6 solution; the pH of the phosphate buffer solution is 6.5-7.2; 1 mol of thiophosphoric acid and 0.01 mol of tri(2-carboxyethyl)phosphine catalyst were added to a bismaleimide-PEG6 solution, the system temperature was raised to 50°C, and the mixture was stirred for 2 hours under nitrogen protection to obtain an antiwear agent precursor; the molar ratio of thiophosphoric acid to bismaleimide-PEG6 was 1:1.1-1.2; 0.55 mol of XC-DAPOL-CPBA was added to the antiwear agent precursor, 0.01 mol of rhodium-carbon catalyst was added, the pH of the system was adjusted to 8.0 with potassium hydroxide solution, the temperature was raised to 60°C, the mixture was refluxed for 10 hours and then cooled to room temperature, and the antiwear agent was washed with deionized water and dried to obtain an antiwear agent.
[0057] Disperse 5 parts of nano black phosphorus in a 5% potassium permanganate solution at 70°C, stir for 2 hours, filter, and wash with deionized water to obtain pretreated nano black phosphorus; add 2 parts of phenylboric acid to the pretreated nano black phosphorus, grind for 5 hours, and dry to obtain modified nano black phosphorus.
[0058] The anti-wear agent 1 and the modified nano black phosphorus are mixed in a mass ratio of 1-17:1, and ground to an average particle size of 170 nm to obtain an anti-wear agent.
[0059] Disperse zirconium oxide in a sulfuric acid solution with a mass fraction of 30%, then filter and dry to obtain sulfated zirconium oxide; disperse 10 parts of Y-type molecular sieve in 200 parts of anhydrous ethanol, then add 0.2 parts of sulfated zirconium oxide thereto, and ultrasonicate at a power of 300 W for 3 hours to obtain a loaded Y-type molecular sieve dispersion; add 13 parts of naphthalene to 6.9 parts of the loaded Y-type molecular sieve dispersion, raise the temperature to 100°C, and add 20 parts of tetradecene within 30 minutes, react for 1 hour, separate the liquids, add deionized water for washing after decantation, separate the liquids again, and distill under reduced pressure to obtain an alkyl naphthalene base oil.
[0060] 25.4 parts of dipentaerythritol were added into a three-necked flask, and then 150 parts of triphenyl sulfide acid were added, the temperature was raised to 100°C, the vacuum degree was adjusted to 98.8 KPa, and then 1 part of concentrated sulfuric acid and 0.5 parts of activated carbon powder were added, and the reaction was carried out for 8 hours to obtain a base oil precursor; 60 parts of lithium water glass with a modulus of 3.5 were dissolved in 940 parts of a sodium hydroxide solution with a mass fraction of 30% to obtain a lithium water glass solution; 150 parts of the lithium water glass solution were added into the base oil precursor and the reaction was continued for 6 hours, and then the base oil was cooled to room temperature and filtered to obtain a dipentaerythritol triphenyl sulfide ester base oil.
[0061] The alkyl naphthalene base oil, the dipentaerythritol triphenyl sulfide ester base oil and the low-viscosity polyalphaolefin are mixed in a ratio of 1:4:5 and then vacuum dried to obtain the base oil.
[0062] 98.6 parts of benzothiazolethiohydroxybenzene bromide are dissolved in an acetone solution to obtain a benzothiazolethiohydroxybenzene bromide solution; the ratio of benzothiazolethiohydroxybenzene bromide to acetone is 1:80; the benzothiazolethiohydroxybenzene bromide solution is heated to 140°C, and 2% of sodium hydroxide and 1.5% of copper chromite catalyst are added thereto to obtain a reaction solution; the reaction solution is stirred for reaction for 12 hours, cooled to room temperature, filtered, washed, and dried to obtain benzothiazolethiohydroxybenzene bromide. 44 parts of N-phenyl-α-naphthylamine are added into a closed reactor, and then 17.2 parts of crotonic acid and 7 parts of a zero-valent ruthenium catalyst are added thereto, and the mixture is reacted at 130° C. for 7 hours to obtain a modified N-phenyl-α-naphthylamine intermediate; benzothiazolethiohydroxyphenol and 2.5 parts of concentrated sulfuric acid are added to the modified N-phenyl-α-naphthylamine intermediate, and the reaction is continued for 4 hours, an equal volume of deionized water is added, and the mixture is washed several times and dried to obtain the modified N-phenyl-α-naphthylamine.
[0063] 90 parts of base oil (three base oils prepared in Example 29), 4.5 parts of antioxidant (modified N-phenyl-α-naphthylamine prepared in Example 42 and hindered phenol 1,1'-disulfide (2-naphthol) mixed in a ratio of 3:1), 1.5 parts of anti-wear agent (anti-wear agent prepared in Example 10), 1 part of corrosion inhibitor (benzotriazole octadecylamine salt, 2-methyl-isothiazol-3 (2H)-one and 2-chloro-1,3-dimethylimidazoline chloride mixed in a ratio of 3:3:2), 0.5 parts of dispersant (high base value sulfurized alkyl phenol salt and ethylene oxide-propylene oxide copolymer mixed in a ratio of 1:1), adjust the temperature to 60°C, stir evenly to obtain a high-performance high-temperature chain oil composition. The base value of the high base value sulfurized alkyl phenol salt is 400 mgKOH / g.
[0064] The detailed information of the preparation process of the embodiment is shown in Table 1.
[0065] Table 1 Detailed information on the preparation process of antiwear agent
[0066]
[0067]
[0068] Comparative Example 1
[0069] The difference from Example 1 is that no modified nano black phosphorus is added, and only abrasive 1 is added as an anti-wear agent.
[0070] Comparative Example 2
[0071] Different from Example 1, the anti-wear agent in Example 1 is replaced by an alkoxy phosphate extreme pressure anti-wear agent, such as P120 Phosphorus Star extreme pressure anti-wear agent manufactured by Shenyang Hualun Oil Chemical Co., Ltd.
[0072] Example 13
[0073] The high-performance high-temperature chain oil compositions prepared in Examples 1-12 and Comparative Examples 1 and 2 were tested for extreme pressure and wear scar diameter. The extreme pressure performance was tested with reference to GB / T 3142-2019 "Determination of Lubricant Load-bearing Capacity by Four-Ball Method", and the MRS-10G lever-type four-ball friction and wear tester was used to test the extreme pressure performance. The wear scar diameter of the high-performance high-temperature chain oil composition was tested with reference to SH / T 0204-92 "Test Method for Anti-Wear Performance of Grease (Four-Ball Machine Method)", and the final test results are shown in Table 2.
[0074] Table 2 Extreme pressure wear resistance test results
[0075]
[0076] The extreme pressure performance of the high-performance high-temperature chain oil composition prepared in the embodiments of the present invention and the comparative examples is P BThe value is 392-1236N, and the wear scar diameter is 0.28-0.51mm. The results of Examples 1-4 show that as the temperature of the sulfur phosphoric acid precursor increases, the extreme pressure performance shows a trend of gradually increasing and then tending to balance, the wear scar diameter first decreases and then increases, and the friction performance increases and then decreases. When the temperature is 85°C, as shown in Example 2, at this time, isooctyl alcohol and phosphorus pentasulfide react completely, which is conducive to the subsequent reaction. The results of Examples 2, 5, and 6 show that as the molar amount of isooctyl alcohol increases, the extreme pressure performance increases and then tends to stabilize, and the wear scar diameter decreases. When the molar ratio of isooctyl alcohol to phosphorus pentasulfide is 1.3:1, isooctyl alcohol not only acts as a reactant, but also plays a role in diluting the system and reducing viscosity, promoting the reaction, so the extreme pressure wear resistance increases. The results of Examples 6-9 show that when the pH of the buffer solution in Example 8 is 6.8, it is most conducive to the synthesis of anti-wear agent 1, thereby improving the extreme pressure wear resistance of the system. The results of Examples 9 and 10 show that as the molar amount of bismaleimide-PEG6 increases, the extreme pressure wear resistance improves, and the introduced boron and nitrogen elements form a friction protection surface during friction, achieving a good wear resistance effect. The results of Examples 10-12 show that when the molar ratio of anti-wear agent 1 to modified nano black phosphorus is 9:1, the extreme pressure wear resistance of the anti-wear agent 1 and modified nano black phosphorus is the best. B The value decreases and the wear scar diameter increases. Comparative Example 2 is replaced with a commercially available alkoxy phosphate extreme pressure anti-wear agent, and both the extreme pressure and wear resistance are reduced.
[0077] Embodiment 14-33
[0078] The detailed information of the base oil preparation process is shown in Table 3. The three types of base oils in Table 3 are alkyl naphthalene base oil, dipentaerythritol triphenyl sulfide ester base oil and low viscosity polyalphaolefin.
[0079] Table 3 Alkyl naphthalene base oil, dipentaerythritol triphenyl sulfide ester base oil and preparation of base oil
[0080]
[0081]
[0082] Comparative Example 3
[0083] The difference from Example 19 is that the high-performance high-temperature chain oil composition is replaced by a foreign brand of oil.
[0084] Embodiment 34
[0085] The alkyl naphthalene base oils prepared in Examples 14-20 were tested for naphthalene conversion. The test results are as follows: Figure 1 shown. Figure 1The results show that in the process of preparing alkyl naphthalene base oil in Examples 14-20, the conversion rate of naphthalene is 90.1%-95.6%. By using sulfuric acid to modify the surface of zirconium oxide, the modified zirconium oxide is loaded in the Y-type molecular sieve, and the sulfated zirconium oxide is evenly dispersed in the Y-type molecular sieve under ultrasonic action. The molecular sieve has a large specific surface area and contains silicon and aluminum elements. The catalytic activity is improved and the naphthalene conversion rate is improved. In Examples 14-17, by changing the amount of sulfated zirconium oxide loaded by the Y-type molecular sieve, as shown in Example 16, the naphthalene conversion rate is the highest when the amount is 0.3 parts. The results of Examples 16 and 18-20 show that when the amount of the loaded Y-type molecular sieve dispersion is 8.7 parts, the naphthalene conversion rate is the highest, which is 95.6%.
[0086] Embodiment 35
[0087] The high-performance high-temperature chain oil compositions prepared in Examples 19, 21-33 and the oil product of Comparative Example 3 were subjected to relevant basic data tests, mainly to determine their kinematic viscosity. Specifically, the kinematic viscosity at 40°C and 100°C was tested with reference to GB / T265-1988 "Method for determination of kinematic viscosity of petroleum products and method for calculation of dynamic viscosity". The test results are shown in Table 4.
[0088] Table 4 Kinematic viscosity test results of high performance high temperature chain oil composition
[0089]
[0090]
[0091] The kinematic viscosity of the high-performance high-temperature chain oil composition prepared in the examples and comparative examples of the present invention at 40°C is 232.4-375.2 mm 2 / s, the kinematic viscosity at 100°C is 24.4-34.8mm 2 / s. The results of Examples 19, 21-26 show that the kinematic viscosity of the chain oil composition changes by changing the amount of triphenyl sulfide acid and lithium water glass solution. In Example 21, when the amounts of the two are 200 parts and 300 parts respectively, the kinematic viscosity is the largest. The results of Example 33 show that by adjusting the amount of alkyl naphthalene base oil, dipentaerythritol triphenyl sulfide ester base oil and polyalphaolefin, the kinematic viscosity at 40°C and 100°C tends to gradually decrease with the increase in the amount of polyalphaolefin base oil. After the introduction of triphenyl sulfide acid, the relative molecular mass of the base oil increases and the viscosity gradually increases; the introduction of lithium water glass causes the base oil to form a gel product, and the viscosity of the chain oil composition gradually increases. By diluting with low-viscosity polyalphaolefin, the viscosity of the high-performance high-temperature chain oil composition prepared by the present invention is slightly higher than the viscosity of the commercial oil of Comparative Example 3.
[0092] Embodiment 36
[0093] The high-performance high-temperature chain oil compositions prepared in Examples 19, 21-33 and the oil products in Comparative Example 3 were subjected to high-temperature and low-temperature resistance performance tests. The viscosity index (VI) of the high-performance high-temperature chain oil composition was measured according to GB / T 2541-1981 "Viscosity Index Calculation Table for Petroleum Products". The flash points of the high-performance high-temperature chain oil compositions of the examples and comparative examples were measured according to GB / T 3536 "Cleveland Open Cup Method for Determination of Flash Point and Fire Point of Petroleum Products". The pour point was measured according to GB / T 3535 "Method for Determining Pour Point of Petroleum Products". The final test results are shown in Table 5.
[0094] Table 5 Test results of viscosity index, flash point and pour point of high performance high temperature chain oil composition
[0095]
[0096]
[0097] The high-performance high-temperature chain oil composition prepared by the examples of the present invention and the comparative examples has a VI value of 89-123, a flash point of 249-279°C, and a pour point of -20 to -31°C. The results of Examples 19, 21-26 show that with the change of the amount of triphenyl sulfide acid and lithium water glass solution introduced, the VI, flash point and pour point change. Among them, under the conditions of Example 25, the amount of triphenyl sulfide acid is 75 parts and the amount of lithium water glass solution is 675 parts. At this time, the VI value is the highest, and the chain oil composition is less affected by temperature. The high-performance high-temperature chain oil composition of Example 24 has the lowest pour point, which is -31°C. While changing the amount of triphenyl sulfide acid and lithium water glass solution, Examples 27-33 also change the mixing ratio between the three base oils. As the amount of low-viscosity polyalphaolefin increases, as shown by the results of Examples 30-33, the overall pour point of the high-performance high-temperature chain oil composition obtained is reduced, and the low-temperature resistance is lower than that of other examples, but it is close to the pour point of the comparative example commercial oil. In summary, the present invention prepares an alkyl naphthalene base oil, and introduces triphenyl sulfide acid and lithium water glass into the dipentaerythritol triphenyl sulfide ester base oil, so that the base oil forms a three-dimensional gel network structure, and the naphthalene ring, benzene ring, silicon, lithium elements, etc. contained therein improve the high temperature resistance and low temperature performance of the high-performance high-temperature chain oil composition, and the performance of the chain oil composition is high.
[0098] Examples 37-43
[0099] The detailed information of the preparation process is shown in Table 6.
[0100] Comparative Example 4
[0101] Different from Example 37, unmodified N-phenyl-α-naphthylamine was used as the antioxidant.
[0102] Embodiment 44
[0103] The high-performance high-temperature chain oil compositions prepared in Examples 37-43 and Comparative Examples 3 and 4 were tested for their antioxidant properties and coking amount. Pressure Differential Scanning Calorimetry (PDSC) was used to simulate the film oxidation of lubricating oil, and the oxidation induction period (230°C isothermal mode) and the initial oxidation temperature (programmed temperature mode) were measured; the inclined plate coking experiment was used to evaluate the sediment formation trend of the oil products, and the final results were expressed as the change in mass per 100mL of oil sample. The final test results are shown in Table 6.
[0104] Table 6 Preparation process of modified N-phenyl-α-naphthylamine, dosage change of anti-wear agent, antioxidant performance and coking amount results
[0105] The high-performance high-temperature chain oil composition prepared by the present invention has an initial oxidation temperature of 237.9-260.5°C, an oxidation induction time of 13.6-82.9min at 210°C, and a coking amount of 12-40mg. In Examples 37-40, as the amount of butyric acid increases, the initial oxidation temperature and oxidation induction time gradually increase, and the coking amount gradually decreases. As the amount of typed chemical substances increases, the antioxidant performance gradually increases, and the high-performance high-temperature chain oil composition is not easy to precipitate from the system during the grinding process. The results of Examples 40-43 show that as the amount of benzothiazolethiohydroxybenzene bromide increases, the antioxidant performance further increases, and the coking amount is significantly reduced. The electron-withdrawing elements and functional groups such as thioether, sulfur, and nitrogen contained in benzothiazolethiohydroxybenzene bromide have the effect of adsorbing and capturing free radicals, thereby improving the antioxidant performance of the high-performance high-temperature chain oil composition. Comparative Example 3 uses unmodified N-phenyl-α-naphthylamine as an antioxidant, and the antioxidant effect is significantly lower than that of the example. In addition, the coking amount is also increased, and precipitation is easy to occur. The antioxidant performance of the commercial oil in Comparative Example 4 is lower than that of the example, and the coking amount is moderate. In summary, the high-performance high-temperature chain oil composition prepared by the present invention has good antioxidant performance, and the coking amount is low, which will not affect the normal use of the equipment.
[0106] Examples 45-55 Comparative Examples 5-8
[0107] The detailed information of the preparation process of the embodiment is shown in Table 7.
[0108] Table 7 Changes in the amount of components in high performance high temperature chain oil composition
[0109]
[0110]
[0111] Embodiment 56
[0112] The high-performance high-temperature chain oil compositions prepared in Examples 45-55 and Comparative Examples 5-8 were subjected to evaporation loss tests and anti-oxidation and coking tests. The evaporation loss was slightly modified according to the following standard, SH / T 0059-1996 "Lubricating Oil Evaporation Loss Determination Method (Noack Method)", and the test conditions were: 250°C, 5h. The anti-oxidation and anti-coking performance tests were carried out with reference to Example 44. The final test results are shown in Figure 2 , Figure 3 and Table 8.
[0113]
[0114]
[0115] like Figure 2 As shown in Table 8, the evaporation loss of the high-performance high-temperature chain oil composition prepared by the present invention is 1.98%-2.86%. Figure 3The results show that the initial oxidation temperature is 235.0-265.4°C, the oxidation induction time is 21.5-98.9min, and the coking amount is 6-38mg. In Examples 45-48, as the amount of base oil increases, the evaporation loss shows a trend of gradually decreasing. The increase in base oil has a protective effect on the substances in the high-performance high-temperature chain oil composition, reduces evaporation loss, improves antioxidant performance, and reduces coking. In Comparative Example 5, the amount of base oil is reduced to 70 parts, and the comprehensive performance of the high-performance high-temperature chain oil composition decreases. The results of Examples 48-50 show that as the amount of antioxidant increases, the antioxidant performance gradually improves, and the modified N-phenyl-α-naphthylamine and the hindered phenol antioxidant play a synergistic role, preventing the high-performance high-temperature chain oil composition from being oxidized. As shown in Comparative Example 8, only modified N-phenyl-α-naphthylamine is used, and hindered phenol is not used as an antioxidant. The initial oxidation temperature is lower than that of Example 45, and the oxidation induction time is reduced and the coking amount is increased. The results of Examples 49, 51, and 52 show that by changing the type of hindered phenol, Example 49 uses 1,1'-sulfodi(2-naphthol) as hindered phenol, in which the benzene ring, sulfur, and multiple phenolic hydroxyl structures improve the overall heat resistance and oxidation resistance of the high-performance high-temperature chain oil composition. The results of Examples 52-55 show that with the increase in the amount of anti-wear agent, the antioxidant performance shows a trend of gradual increase; Comparative Example 7 does not add an anti-wear agent, and the antioxidant performance is reduced; The modified anti-wear agent and the modified nano black phosphorus composed of anti-wear agent, synergistic with the antioxidant, have a good antioxidant effect. However, when the amount of anti-wear agent continues to increase, as shown in Example 55, the amount of coking increases. As the amount of anti-wear agent increases, during the use of the high-performance high-temperature chain oil composition, the amount of coking increases with the precipitation of modified black phosphorus. Comparative Example 6 does not add an antioxidant, the initial oxidation temperature decreases, the oxidation induction time decreases, and the amount of coking increases. The evaporation loss of Examples 54 and 55 is lower than that of Examples 52 and 53. This may be because as the amount of anti-wear agent increases, the phenylboric acid in the modified nano black phosphorus reacts with the free hydroxyl groups in the base oil under high temperature conditions to cap the hydroxyl groups and reduce the evaporation of the substance.
[0116] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high-performance high-temperature chain oil composition, characterized in that: The following steps are involved: 70-92 parts of base oil, 0-4.5 parts of antioxidant (modified N-phenyl-α-naphthylamine and hindered phenol mixed in a ratio of 3:1), 0-2.5 parts of anti-wear agent, 1 part of anti-corrosion agent, and 0.5 parts of dispersant are mixed, the temperature is adjusted to 60° C., and stirred evenly to obtain the high-performance high-temperature chain oil composition; The anti-wear agent is a mixture of an anti-wear agent 1 and modified nano black phosphorus in a mass ratio of 1-17:1; the heating temperature of the thiophosphoric acid precursor in the anti-wear agent 1 is 60-95°C; the molar ratio of isooctyl alcohol to phosphorus pentasulfide is 1.1-1.3:1; the pH of the phosphate buffer solution in the maleimide-PEG6 solution is 6.5-7.2; the molar ratio of thiophosphoric acid to bismaleimide-PEG6 is 1:1.1-1.2; The base oil is obtained by mixing alkyl naphthalene base oil, dipentaerythritol triphenyl sulfide ester base oil and low-viscosity polyalphaolefin in a ratio of 1-4:1-6:5-13 and then vacuum drying; The alkyl naphthalene base oil is prepared by dispersing a Y-type molecular sieve in anhydrous ethanol, adding 0.1-0.4 parts of sulfated zirconium oxide thereto, and ultrasonically obtaining a supported Y-type molecular sieve dispersion; adding naphthalene and tetradecene to 5.5-8.7 parts of the supported Y-type molecular sieve dispersion, separating the liquids after the reaction, and performing reduced pressure distillation to obtain the supported Y-type molecular sieve dispersion; The dipentaerythritol triphenyl sulfide ester base oil is obtained by reacting dipentaerythritol, 0-250 parts of triphenyl sulfide acid, concentrated sulfuric acid and 150-750 parts of lithium water glass solution; The modified N-phenyl-α-naphthylamine is obtained by reacting 98.6-102.4 parts of benzothiazolethiohydroxybenzene bromide, a copper chromite catalyst, 44 parts of N-phenyl-α-naphthylamine and 16.8-17.5 parts of crotonic acid.
2. The method for preparing a high-performance high-temperature chain oil composition according to claim 1, characterized in that: The preparation method of the anti-wear agent comprises the following steps: in terms of molar ratio, reacting the isooctyl alcohol with 1 / 3 of the phosphorus pentasulfide to obtain a thiophosphoric acid precursor; heating the thiophosphoric acid precursor, adding 2 / 3 of the phosphorus pentasulfide thereto, and reacting to obtain the thiophosphoric acid; adding the thiophosphoric acid and tris(2-carboxyethyl)phosphine catalyst to the bismaleimide-PEG6 solution, raising the system temperature to 50°C, and stirring for 2 hours under nitrogen protection to obtain an anti-wear agent precursor; adding XC-DAPOL-CPBA to the anti-wear agent precursor, adding a catalyst, adjusting the pH, and then raising the temperature, and reflux reaction for 10 hours to obtain the anti-wear agent one; mixing the anti-wear agent one and the modified nano black phosphorus, and grinding to an average particle size of 170 nm to obtain the anti-wear agent.
3. The method for preparing a high-performance high-temperature chain oil composition according to claim 1, characterized in that: The preparation method of the modified nano black phosphorus is as follows: dispersing the nano black phosphorus in a potassium permanganate solution at 70° C., stirring for 2 hours, filtering, and washing with deionized water to obtain pre-treated nano black phosphorus; adding phenylboric acid to the pre-treated nano black phosphorus, grinding for 5 hours, and drying to obtain the modified nano black phosphorus.
4. The method for preparing a high-performance high-temperature chain oil composition according to claim 1, characterized in that: The preparation method of the dipentaerythritol triphenyl sulfide ester base oil is as follows: adding the dipentaerythritol into a three-necked flask, then adding the triphenyl sulfide acid, raising the temperature to 100° C., adjusting the vacuum degree to 98.8 KPa, then adding the concentrated sulfuric acid and activated carbon powder, and reacting for 8 hours to obtain a base oil precursor; dissolving lithium water glass in a sodium hydroxide solution to obtain the lithium water glass solution; adding the lithium water glass solution to the base oil precursor and continuing to react for 6 hours, then cooling to room temperature, and filtering to obtain the dipentaerythritol triphenyl sulfide ester base oil.
5. The method for preparing a high-performance high-temperature chain oil composition according to claim 4, characterized in that: The modulus of the lithium water glass is 3.
5.
6. The method for preparing a high-performance high-temperature chain oil composition according to claim 1, characterized in that: The preparation method of the modified N-phenyl-α-naphthylamine is as follows: dissolving the benzothiazolethiohydroxybenzene bromide in an acetone solution to obtain a benzothiazolethiohydroxybenzene bromide solution; heating the benzothiazolethiohydroxybenzene bromide solution to 140°C, adding sodium hydroxide and the copper chromite catalyst thereto to obtain a reaction solution; stirring the reaction solution for 12 hours, cooling it to room temperature and then filtering it, then washing and drying it to obtain benzothiazolethiohydroxyphenol; adding the N-phenyl-α-naphthylamine into a closed reactor, then adding the crotonic acid and the zero-valent ruthenium catalyst thereto, reacting at 130°C for 7 hours to obtain a modified N-phenyl-α-naphthylamine intermediate; adding the benzothiazolethiohydroxyphenol and concentrated sulfuric acid to the modified N-phenyl-α-naphthylamine intermediate, continuing the reaction for 4 hours, adding deionized water, washing it several times and then drying it to obtain the modified N-phenyl-α-naphthylamine.
7. The method for preparing a high-performance high-temperature chain oil composition according to claim 1, characterized in that: The antioxidant is used in an amount of 3.8-4.5 parts.
8. The method for preparing a high-performance high-temperature chain oil composition according to claim 1, characterized in that: The amount of the anti-wear agent is 1.5-2.5 parts.
9. The method for preparing a high-performance high-temperature chain oil composition according to claim 1, characterized in that: The hindered phenol is any one of 1,1'-dithiodi(2-naphthol), 2,2',4,4'-tetrahydroxydiphenyl sulfide and 2,2-dihydroxydiphenyl sulfide.
10. A high-performance high-temperature chain oil composition, characterized in that: The high-performance high-temperature chain oil composition comprises a base oil, an antioxidant, an anti-wear agent, a corrosion inhibitor and a dispersant; the high-performance high-temperature chain oil composition is prepared by the preparation method according to any one of claims 1 to 9; the high-performance high-temperature chain oil composition P B The value is 392-1236N, the wear scar diameter is 0.28-0.51mm; the conversion rate of naphthalene in the alkyl naphthalene base oil is 90.1%-95.6%; the kinematic viscosity of the high-performance high-temperature chain oil composition at 40°C is 232.4-375.2mm 2 / s, kinematic viscosity at 100℃ is 24.4-34.8mm 2 / s; the VI value of the high-performance high-temperature chain oil composition is 89-123, the flash point is 249-279°C, and the pour point is -20 to -31°C; the initial oxidation temperature of the high-performance high-temperature chain oil composition is 237.9-260.5°C, the oxidation induction time at 210°C is 13.6-82.9min, and the coking amount is 12-40mg; the evaporation loss of the high-performance high-temperature chain oil composition is 1.98%-2.86%, the initial oxidation temperature is 235.0-265.4°C, the oxidation induction time is 21.5-98.9min, and the coking amount is 6-38mg.
Citation Information
Patent Citations
High-temperature chain oil composition and its preparation method
CN105838484B
A high-temperature chain oil composition and its manufacturing method
CN106590847B
A high-temperature chain oil composition and its preparation method
CN107304377B
A high-temperature chain oil composition and its preparation method
CN107304378B
High-temperature chain oil and preparation method thereof
CN101117609A